CSR Integration, Non-Financial KPIs, and Firm Value: Evidence from Renewable Energy Companies - Sarsiti Sarsiti; Fadhillla Husna (CV. Get Press Indonesia, 2026)
This study examines the effect of Corporate Social Responsibility (CSR) integration and non-financial key performance indicators (non-financial KPIs) on firm value in the renewable energy sector. Although sustainability disclosure has become increasingly institutionalized in the energy transition era, empirical evidence on whether CSR integration translates into measurable financial outcomes for renewable energy firms remains inconclusive. This research employs an unbalanced panel dataset of 30 publicly listed renewable energy companies observed over the 2020–2024 period, resulting in 150 firm-year observations. Firm value is measured using Tobin's Q, while CSR Integration is measured through a composite disclosure index derived from GRI Standards, and non-financial KPIs are measured through a composite index covering environmental efficiency, workforce metrics, innovation intensity, and stakeholder engagement. Firm size, leverage, and return on assets are included as control variables. Panel data regression is estimated using Pooled Ordinary Least Squares (OLS), Fixed Effects, and Random Effects models, with model selection guided by the Chow, Hausman, and Lagrange Multiplier tests. The Random Effects model is the most appropriate specification. Non-financial KPI integration exerts a positive and statistically significant effect on firm value, whereas CSR Integration shows a positive but statistically weaker association. Leverage is negatively associated with firm value, while profitability (ROA) is positively associated. These findings suggest that integrating sustainability metrics into firm strategy is more value-relevant than symbolic CSR disclosure. This study distinguishes disclosure-based CSR integration from operationally embedded, performance-based non-financial KPIs, clarifying which dimension of sustainability performance is genuinely value-relevant for renewable energy firms.